The Impact of Narcotic Abuse on Users Mental Health: A Literature Review - Mohamad Sujatno Setiawan; Zudan Arief Fakrulloh (International Journal of Social Service and Research, 2026)
Narcotic abuse remains a critical global public health issue that affects not only physical health but also psychological well-being, cognitive functioning, and social relationships. The misuse of narcotic substances has been associated with various mental health disorders, including depression, anxiety, psychosis, emotional instability, and cognitive impairment. However, the complex relationship between narcotic abuse and mental health requires comprehensive examination because the two conditions may influence one another through biological, psychological, and social mechanisms. This study aimed to examine the impact of narcotic abuse on users’ mental health by synthesizing existing scientific evidence on its psychological consequences, contributing factors, and potential intervention strategies. This study employed a qualitative literature review method. Relevant scientific publications retrieved from reputable databases, including Scopus, PubMed, and Google Scholar, were analyzed according to predefined inclusion criteria. The findings indicated that narcotic abuse significantly increased the risk of mental health problems, particularly depression, anxiety disorders, psychotic symptoms, impaired cognitive functioning, and a reduced quality of life. The findings also demonstrated that the relationship between substance abuse and mental disorders was bidirectional: psychological distress may encourage narcotic use, while prolonged exposure to narcotic substances may exacerbate existing mental health conditions. In conclusion, narcotic abuse should be addressed through an integrated biopsychosocial approach involving medical treatment, psychological support, rehabilitation programs, and preventive strategies. A comprehensive understanding of this relationship is essential for developing effective policies and interventions that improve mental health outcomes among individuals who use narcotics